A study on comparison between common object request broker arcmtecture (CORBA) and XYBASE message broker (XMB) / Inna Mohd Izman - Mohd Izman, Inna (2003)
This paper presents a study on comparisons between Common Object Request Broker Architecture (CORBA) and XYBASE Message Broker (XMB). This study will be comparing from the services area, whereby it will highlight on messaging services. In addition it will also touch on the advantages and disadvantages of each of the middleware. Messaging services has been select to be highlight due to the significance of sharing information in every scenario. Besides that, messaging solution is important in order for the businesses to address their unique set of systems, business requirements and also their information technology (IT) resources. This study is to provide a guideline in choosing a better middleware especially for enterprises. In the fourth chapters, it provides information on research methodology, whereby it will describe on the data collection method. The method is used to gather all the related information about the research. The findings include from the Internet, library research, and interviews. While the finding chapters, presents the summary of the comparison that has undergone. In conclusion, it will come up with a summarization on the comparisons and guideline. Hope that with the guideline that been produced in the end of the study; will help the enterprises in choosing middleware.